The Transformation of MSMEs in Nganjuk into Independent Exporters through Innovation and Access to Global Trade Information - Budiarti, Anindhyta; Kurnia, Kurnia; Subardjo, Anang; Ramadhani, Yesa Cahayaning (Doctoral Program of Social Science, Pasundan University, 2025)
The transformation of Micro, Small, and Medium Enterprises (MSMEs) in Nganjuk into independent exporters represents a significant shift towards enhancing local economic growth through innovation and global market access. As the global trade landscape continues to evolve, MSMEs play a crucial role in driving economic development, particularly in rural and regional areas. By leveraging innovative practices, MSMEs in Nganjuk have been able to diversify their products and services, making them more competitive in the international market. This transformation is supported by improved access to global trade information, which enables businesses to understand market trends, customer demands, and regulatory requirements in various countries. Through various training programs, digital tools, and partnerships with government agencies and international trade organizations, MSMEs in Nganjuk have developed the necessary skills and resources to expand beyond domestic markets. This process not only increases the export potential of these businesses but also contributes to the overall economic resilience of the region. The focus on innovation and information access has allowed Nganjuk's MSMEs to adapt to the challenges of a rapidly changing global economy. The success of these businesses as independent exporters is a testament to the potential of small and medium enterprises to compete in the global market, driving sustainable economic growth, job creation, and poverty reduction. This case study highlights the importance of continuous support, capacity building, and fostering global connections to enable MSMEs to thrive in an increasingly interconnected world.